Spontaneous renal allograft rupture without acute rejection - Busi, N.; Capocasale, E.; Mazzoni, et al., M.P. (Acta Biomedica Atenei Parmensis, 2004)
Renal allograft rupture (RAR) is a rare but potentially serious complication in the transplanted recipients. The most common cause is acute rejection.We report four cases (0.5%) of RAR occurred in a series of 778 consecutive kidney transplantations due to severe acute tubular necrosis and renal vein thrombosis with no evidence of acute rejection. Transplant nephrectomy was performed in three patients, whereas graft repair was achieved in one patient. These data suggest that RAR may be associated with renal vein thrombosis or severe acute tubular necrosis in absence of acute rejection. Frequently nephrectomy is necessary, but conservative surgical treatment should be attempted to preserve the allograft in selected cases.